Beginning Nokia Apps Developmen - Rischpater, Ray (Apress, 2012)
Popular acceptance of the smartphone has brought technology once only previously imagined in science fiction to today’s reality. You can now use the small electronic device that used to be a simple cell phone to manage your calendar, listen to music, take pictures, provide maps and navigation, and browse the Internet—and still make a phone call. The technology that links you to the vast information store on the Internet any time and anywhere is perhaps the greatest revolution in information access the world has seen. Not only available to the developed nations where we expect to see high-end smartphones, these devices are also widely available in developing nations, where they are often the primary device people use to access the Internet. The convergence of low-cost high performance processors, cheap memory, and wireless networking is only some of the technology that make the smartphone possible. The widespread use of open mobile computing platforms is the key to the smartphone’s success. These platforms have opened the door for third parties (that’s you!) to write software applications for these mobile computing platforms quickly and inexpensively. Applications are no longer the exclusive domain of the device manufacturer. Now, anyone can imagine an application and implement it. These applications are with you everywhere that you carry your cell phone, and can take advantage of positioning information and wireless connectivity provided by the phone. It is this ability for anyone to create an application that has made the cell phone the truly wonderful device of tomorrow.